Proposed Amendments to the Wildlife Protection Law of the People's Republic of China - Lihong Gao (Universitat Autonoma de Barcelona. Facultat de Dret, 2020)
The outbreak of COVID-2019 has focused public attention on China's wildlife-related legal regimes, such as the regulatory regime for wildlife hunting and trade and the animal epidemic prevention regime, which is complex, with the Wildlife Protection Law as the core. On February 24, the standing committee of the National People's Congress (NPC) issued an emergency legal document, the Decision, which has the effect of banning wildlife consumption, guiding public awareness, and regulating the overall legal system, and directly initiates the revision of the Wildlife Protection Law. On 21 October 2020, the Wildlife Protection Law (draft amendment) was announced. Based on the Decision and the Draft, this paper believes that in future revisions of the Wildlife Protection Law the main focus should be on changing the form of state ownership, establishing a pluralistic protection system, increasing legal penalty, coordinating with other legislation, and concern for individual animal welfare.